Machine learning for acute kidney injury: Changing the traditional disease prediction mode - Yu, Xiang; Ji, Yuwei; Huang, Mengjie; Feng, Zhe (Frontiers in Medicine, 2023)
Acute kidney injury (AKI) is a serious clinical comorbidity with clear short-term and long-term prognostic implications for inpatients. The diversity of risk factors for AKI has been recognized in previous studies, and a series of predictive models have been developed using traditional statistical methods in conjunction with its preventability, but they have failed to meet the expectations in limited clinical applications, the rapid spread of electronic health records and artificial intelligence machine learning technology has brought new hope for the construction of AKI prediction models. In this article, we systematically review the morbidity characteristics of AKI patients, changes in definitions and diagnostic criteria, known morbidity risk factors, common characteristics of traditional scoring systems, definition and classification of machine learning methods, modeling ideas and evaluation methods, and the characteristics and current status of modeling studies. According to the modeling objectives, we subdivided them into critical care medical setting models, all medical environment models, special surgery models, special disease models, and special nephrotoxin exposure models. As the first review article to comprehensively summarize and analyze machine learning prediction models for AKI, we aim to objectively describe the advantages and disadvantages of machine learning approaches to modeling, and take this as a clue to guide and stimulate more in-depth exploration in the future , which will ultimately help to improve the overall status of AKI diagnosis and treatment.